Comparative Analysis of SES and SMA Methods for Prediction of Raw Materials for Tempe House Products Yusnita - Yuliana, Siska; Fauziah, Rizky; Ramadhani, Andrew (Sistemasi: Jurnal Sistem Informasi, 2024)
Forecasting is an estimate of future events on the basis of past time patterns and the use of policies for projections with past patterns. With forecasting, the company can make the right policy or decision for the raw materials to be produced. Therefore, forecasting is very important for Rumah Tempe Yusnita so that the amount of raw material inventory is not excessive or insufficient in production, the more inventory results in spoilage that occurs and can also affect losses to Rumah Tempe Yusnita. The Single Exponential Smoothing and Single Moving Average methods with the comparison of these methods will obtain both methods that can provide greater flexibility, using the SES method to respond to rapid changes and SMA to compensate or flatten larger fluctuations. Prediction analysis of raw materials using the SES and SMA methods at Rumah Tempe Yusnita can help owners predict raw materials that produce information quickly, precisely and accurately.